Frequency of Prediabetes in Patients Presenting for Routine Checkup in Outpatient Department - Ali, Sajid; Batool, Uzma (Biological and Clinical Sciences Research Journal, 2025)
Prediabetes is an intermediate metabolic state of elevated blood glucose levels that fall below the threshold for diabetes diagnosis. Often asymptomatic, it serves as an early warning sign for the future development of type 2 diabetes. Objective: To determine the frequency of prediabetes and evaluate associated demographic and lifestyle risk factors among patients attending routine outpatient checkups. Methods: This cross-sectional study was conducted at the Department of Medicine, PAEC General Hospital, Islamabad, from December 2024 to May 2025. A total of 201 patients aged 20–70 years, attending for routine checkups, were included through non-probability consecutive sampling. HbA1c was measured to assess glycemic status. Prediabetes was defined as HbA1c levels between 5.7% and 6.4%. Results: Prediabetes was detected in 26 out of 201 patients (12.9%). A statistically significant association was found between prediabetes and both BMI ≥30 (p = 0.03) and sedentary lifestyle (p = 0.048). No significant associations were observed with gender, age, smoking status, place of residence, or income. Logistic regression analysis confirmed obesity and physical inactivity as independent predictors of prediabetes. Conclusion: It is concluded that the frequency of undiagnosed prediabetes is substantial in patients presenting for routine OPD checkups. Obesity and sedentary lifestyle were key risk factors. Routine HbA1c screening should be integrated into outpatient settings to enable early detection and preventive care.